The Legacy of Sriwijaya in South Sumatra as a Learning Resource for History Teachers in Muaraenim Regency - Susanti, L.R. Retno; Hudaidah, Hudaidah; Pahlevi, Muhammad Reza; Yati, Risa Marta (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research directs history teachers to utilize local history learning resources related to historical material, specifically in the Muaraenim Regency. The methods used are lectures, questions, and answers or discussions, as well as working on pre-test and post-test questions. The results of the socialization show that history teachers who have participated in PKM activities have been given direction in utilizing past relics with local historical nuances. History teachers can relate historical material to the context of the material being taught by involving local history in their area. Like the use of history in Muaraenim Regency, the existence of the Bumiayu Temple Site can be used as a source of historical learning, because it has historical values. Efforts to learn local history are used to instill a sense of love for the surrounding area.